A hematoporphyrin and indocyanine green co-delivery system with NIR triggered-controllable photoactivities for photodynamic therapy. (July 2018) - Li, Ziying; Lv, Tingting; Zhang, Yingying; Xu, Liang; Zhang, Lu; Wang, Xiuying; Chen, Haijun; Gao, Yu
Abstract: Photodynamic therapy (PDT) was hindered by the poor water solubility and long-enduring photoactivities of photosensitizers. Here, we developed a novel controllable photodynamic agent CPHI based on β-cyclodextrin modified polyamidoamine (PAMAM) dendrimer (CP) co-delivery of indocyanine green (ICG) and hematoporphyrin (HP). The CPHI possessed appropriate particle sizes and zeta potentials, considerable photostability, and NIR-triggered release property. The fluorescence of HP could be quenched by ICG when HP and ICG were co-loaded inside the CP, and the quenching efficiency was related with the weight ratio of HP and ICG. When the feeding weight proportion of HP and ICG is 1/10, the fluorescence of HP was quenched by 87.3% in CPHI. Under 808 nm laser irradiation, the ICG in CP was degraded, and the fluorescence of HP could recover. The recovered HP was capable of generating reactive oxygen species (ROS) for PDT with 606 nm laser irradiation. The cytotoxicity and cell apoptosis studies showed that CPHI could effectively induce MCF-7 cells apoptosis with PDT effects under 808/660 nm laser. These results suggested that CPHI could be an efficient cancer therapeutic agent for controllable PDT with low dark toxicity. Highlights: A nanomedicine CPHI for controllable PDT with low dark toxicity was synthesized. The fluorescence of HP quenched by ICG could recover with 808 nm laser irradiation. The recovered HP was capable of generating ROS for PDT with 606 nm laser irradiation.